Can Self-Esteem Help Teens Resist Unhealthy Influence of Materialistic Goals Promoted By Role Models? - Zawadzka, Anna Maria; Borchet, Judyta; Iwanowska, Magdalena; Lewandowska-Walter, Aleksandra (Frontiers in Psychology, 2022)
The aim of the paper was to examine the role of self-esteem in resisting the influence of four social materialism role models (mother, father, peers, and media) in adolescents (aged 13-16). Previous studies showed a negative correlation between psychological health of teens and materialism, one of whose main sources is social modeling of materialism. Two studies were carried out. The first, correlational study, was conducted on target teens as well as their mothers, fathers, and peers of their choice. It examined if self-esteem is a moderator of the relation between social materialism role models (mothers, fathers, peers, and media) and teens’ materialism. The second, experimental study, was conducted on target teens only. It examined how boosting teens’ self-esteem and activating social materialism role models (mothers, fathers, peers, and media) may affect teens’ materialism. Study 1 showed a significant interaction effect of self-esteem and the peers’ materialism on teens’ materialism. The interaction effects of self-esteem and other role models (parents and media) were not significant. Study 2 showed that elevated self-esteem lowered the influence of peers’ materialism on teens’ materialism. The results were not significant when other role models (parents and media) were analyzed. The results obtained in the presented studies indicate that teens’ self-esteem may have an important role in resisting the influence of materialism role model of peers’. Practical implications of the studies for teens’ psychological health are also discussed.